Mycorrhization and chemical seed priming boost tomato stress tolerance by changing primary and defence metabolic pathways - Giovannini, Luca; Pagliarani, Chiara; Cañizares, Eva; Sillo, Fabiano; Chitarra, Walter; De Rose, Silvia; Zampieri, Elisa; Ioannou, Andreas; Spanos, Alexandros; Vita, Federico; González Guzmán, Miguel; Fotopoulos, Vasileios; et al. (My University, 2025)
Priming modulates plant stress responses before the stress appears, increasing the ability of the primed plant to endure adverse conditions and thrive. In this context, we investigated the effect of biological (i.e. arbuscular mycorrhizal fungi, AMF) agents and natural compounds (i.e. salicylic acid applied alone or combined with chitosan) against water deficit and salinity on a commercial tomato genotype (cv. Moneymaker). Effects of seed treatments on AMF colonization were evaluated, demonstrating the possibility of using them in combination. Responses to water and salt stresses were analysed on primed plants alone or in combination with the AMF inoculum in soil. Trials were conducted on potted plants by subjecting them to water deficit or salt stress. The effectiveness of chemical seed treatments, both alone and in combination with post-germination AMF inoculation, was investigated using a multidisciplinary approach that included ecophysiology, biochemistry, transcriptomics, and untargeted metabolomics. Results showed that chemical seed treatment and arbuscular mycorrhizal symbiosis modified the tomato response to water deficit and salinity triggering a remodelling of both transcriptome and metabolome, which ultimately elicited the plant antioxidant and osmoprotective machinery. The plant physiological adaptation to both stress conditions improved, confirming the success of the adopted approaches in enhancing stress tolerance.
Keywords: Arbuscular mycorrhizal symbiosis; chemical priming; salinity; metabolomics; water deficit; transcriptomics